Linguistic, Sociocultural Constructivism as a Founding Pedagogical Theory for General Studies - Córdoba, María Elena (2020)
This article aims to highlight and analyze some characteristics of constructivism and General Studies to build conceptual bridges and methodological encounters between them. It also aims to generate reflection that allows identifying, specifically, the benefits of linguistic, sociocultural constructivism as an appropriate theoretical foundation for General Studies epistemology, whose purpose is to develop ethical citizens, with critical thinking, and sense of the common good, among other characteristics. A horizontal relationship that General Studies proposed and a student-teacher bond, which allows recognizing oneself and others as persons, cannot be founded upon any pedagogical theory. Therefore, it is possible to create bonds with this form of constructivism, in which the process of teaching and learning implies joint activities between students and teachers and occurs around contents and teaching actions through the structuring of those activities and the semiotic resources present in the speech of people involved. Finally, a parallel can be established between linguistic, sociocultural constructivism and General Studies, as long as a position is adopted for the conception of learning to be superseded from disciplines independently, prioritizing, at the same time, the means with which knowledge is built, i.e., language, in addition to other similarities that lead to considering that position to be worthy of being taken into account as a founding theory for teaching practice in General Studies.